Aberration generators in tandem - Ojeda Castaneda, Jorge; Barragán-Chávez, Ana L.; Gómez-Sarabia, Cristina M. (Photonics Letters of Poland, 2015)
We discuss the use of a pair of phase masks, which have both radial and helical variations, for optically implementing wavefront aberration generator. We show that by using these masks one can change continuously the aberration coefficients of both symmetric and asymmetric aberrations. Some numerical simulations illustrate our proposed procedure. Full Text: PDF References D. L. Fridge, "Aberration synthesizer", J. Opt. Soc. Am. 50, 87 (1960). DirectLink A. Buchroeder and R. Brian Hooker, "Aberration generator", Appl. Opt. 14, 2476 (1975). CrossRef N. López-Gil, H. C. Howland, B. Howland, N. Charman and R. Applegate, "Generation of third-order spherical and coma aberrations by use of radially symmetrical fourth-order lenses", J. Opt. Soc. Am. A 15, 2563 (1998). CrossRef I. A. Palusinski, J. M. Sasián, and J. E. Greivenkamp, "Lateral-shift variable aberration generators", Appl. Opt. 38, 86 (1999). CrossRef Eva Acosta and Salvador Bará, "Variable aberration generators using rotated Zernike plates", J. Opt. Soc. Am. A 22(9), 1993?1996 (2005). CrossRef Eva Acosta and José Sasián, "Phase plates for generation of variable amounts of primary spherical aberration", Opt. Express 19, 13171 (2011). CrossRef Jorge Ojeda-Casta-eda, J. E. A. Landgrave and Cristina M. Gómez-Sarabia, "Conjugate phase plate use in analysis of the frequency response of imaging systems designed for extended depth of field", Appl. Opt. 47, E99 (2008). CrossRef Jorge Ojeda-Castaneda, "Tunable focalizers: axicons, lenses, and axilenses", SPIE Proceedings 8833, 883306 (2013). CrossRef Jorge Ojeda-Castaneda, Sergio Ledesma, and Cristina M. Gómez-Sarabia, "Tunable apodizers and tunable focalizers using helical pairs", Photonics Letters of Poland 5, 20 (2013). CrossRef Harold H. Hopkins, Wave theory of aberrations (Oxford, Oxford University Press, 1950). B. R. A. Nijboer, The diffraction theory of aberrations, (Ph.D. dissertation, University of Groningen, The Netherlands, 1942). J. Y. Wang and D. E. Silva, "Wave-front interpretation with Zernike polynomials", Appl. Opt. 19, 1510?1518 (1980). CrossRef S. C. Biswas and J.-E. Villeneuve, "Diffraction of a laser beam by a circular aperture under the combined effect of three primary aberrations", Appl. Opt. 25, 2221?2232 (1986). CrossRef